Indium(iii) chloride catalyzed highly diastereoselective domino synthesis of indenodithiepines and indenodithiocines. Issue 4 (24th November 2014) - Muthusamy, Sengodagounder; Sivaguru, Manickasamy; Suresh, Eringathodi
Abstract : An atom-economical diastereoselective synthesis of indenodithiepines and indenodithiocines has been developed via a domino reaction of propargylic alcohols and dithioacetals in the presence of InCl3 as a catalyst. Abstract : An atom-economical diastereoselective synthesis of indenodithiepines and indenodithiocines has been developed via a domino reaction of propargylic alcohols and dithioacetals in the presence of InCl3 as a catalyst. A range of functionalized dithiepines and dithiocines, fused to the indene ring, were obtained in good to excellent yields under mild conditions.